Audio Visual Aid’s Development of Health Promotion Media With Design Thinking at Nutrition Care Center - Amareta, Dahlia Indah; Perwiraningrum, Dhyani Ayu; Arifianto, Aji Seto; Suryana, Arinda Lironika; Saputri, Dinar Suksmayu (Indonesian Journal Publisher, 2024)
Teaching Factory Nutrition Care Center (NCC) is a synergistic product of the Jember State Polytechnic and the world of business and industry (DUDI). The development of NCC supports student practice learning in conducting nutrition interventions. The research aims to develop an efficient and attractive NCC-promotive educational media. This research is a Research and Development (R&D) with the approach that is used design thinking. It requires a designer to be able to analyze a problem, express creative ideas, experiment in making a prototype, to collect the proper feedback regarding the media created. The study results show that the audio-visual media that will be developed are the NCC mascot, profile videos, and nutrition education videos. Through the ideate and prototype stages are an egg mascot called Si Nucca, an acronym for the Nutrition Care Center. The character of eggs describes foods with high nutritional value and are affordable by the community. The results of media validation by the material and media validators got good results ( score of 4.7). Acceptance test results show a score of 4.47 with a good interpretation on the aspects of effectiveness, attractiveness and efficiency. The conclusion is that the audio-visual media that has been developed is feasible to be tested on the public.